Molecular cloning and characterization of novel phytocystatin gene from turmeric, Curcuma longa - Chan, Seow Neng; Abu Bakar, Norliza; Mahmood, Maziah; Ho, Chai Ling; Shaharuddin, Noor Azmi (Hindawi Publishing Corporation, 2014)
Phytocystatin, a type of protease inhibitor (PI), plays major roles in plant defense mechanisms and has been reported to show antipathogenic properties and plant stress tolerance. Recombinant plant PIs are gaining popularity as potential candidates in engineering of crop protection and in synthesizing medicine. It is therefore crucial to identify PI from novel sources like Curcuma longa as it is more effective in combating against pathogens due to its novelty. In this study, a novel cDNA fragment encoding phytocystatin was isolated using degenerate PCR primers, designed from consensus regions of phytocystatin from other plant species. A full-length cDNA of the phytocystatin gene, designated CypCl, was acquired using 5′/3′ rapid amplification of cDNA ends method and it has been deposited in NCBI database (accession number KF545954.1). It has a 687 bp long open reading frame (ORF) which encodes 228 amino acids. BLAST result indicated that CypCl is similar to cystatin protease inhibitor from Cucumis sativus with 74% max identity. Sequence analysis showed that CypCl contains most of the motifs found in a cystatin, including a G residue, LARFAV-, QxVxG sequence, PW dipeptide, and SNSL sequence at C-terminal extension. Phylogenetic studies also showed that CypCl is related to phytocystatin from Elaeis guineensis.